Extensive Type V Aplasia Cutis Congenita Without Fetus Papyraceus or Placental Infarction: A Rare Case - Effendi RMRA; Nuraeni L; Diana IA; Gondokaryono SP; Gunawan H; Dwiyana RF (Dove Medical Press, 2021)
Raden Mohamad Rendy Ariezal Effendi, Lita Nuraeni, Inne Arline Diana, Srie Prihianti Gondokaryono, Hendra Gunawan, Reiva Farah Dwiyana Department of Dermatology and Venereology, Faculty of Medicine Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Raden Mohamad Rendy Ariezal EffendiDepartment of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, 40161, West Java, IndonesiaEmail rendy.ariezal.effendi@unpad.ac.idAbstract: Aplasia cutis congenita (ACC) is a congenital disorder characterized by the absence of epidermis, dermis, and sometimes subcutaneous tissue and bone. There are nine types of ACC based on the number and location of the lesions as well as the presence or absence of associated deformities, with type I ACC being the most common. Type V affects the trunk with a characteristic pattern resembling the "H" letter of the alphabet, generally accompanied by fetus papyraceus (death of one of the twin fetuses) or placental infarction. Type V ACC without fetus papyraceus and placental infarction is a rare case. We reported a case of type V ACC in a 3-day-old baby girl, with clinical manifestation of extensive ulcers on the scalp, back, buttocks, and both lower extremities, in an "H"-shaped pattern, with history of placenta accreta, but no fetus papyraceus or placental infarction was found. The patient received dialkyl carbamoyl chloride hydrophobic swab with hydrogel (Sorbact® gel dressing-BSN Medical) and hydrocolloid wound dressing with good response, as indicated by the wounds becoming dried up, leaving an atrophic scar. Complete epithelialization was achieved in 72 days. The cause of type V ACC remains not completely understood. The diagnosis of ACC can be established based on clinical manifestations. Further examination is required if extracutaneous involvement is suspected. Early identification of the etiology of the lesions and appropriate investigation and treatment, including conservative wound management, are needed so that aplastic lesions can heal successfully, although cosmetic repair may be required at a later stage.Keywords: aplasia cutis congenita, fetus papyraceus, placenta accreta